Comorbidities in Cushing’s disease - Sharma, S. T. (Pituitary, 2015)
INTRODUCTION: Cushing’s disease is a rare disorder characterized by overproduction of ACTH from a pituitary adenoma leading to hypercortisolemia that in turn leads to increased morbidity and mortality. METHODS: Here we review the comorbidities associated with Cushing’s disease and their impact on quality of life and mortality. RESULTS: Recent evidence suggests that correction of hypercortisolemia may not lead to complete resolution of comorbidities associated with this condition. In particular, increased cardiovascular risk may persist despite long-term remission of hypercortisolemia. This may be related to persistence of visceral adiposity, adverse adipokine profile, glucose intolerance, hypertension, dyslipidemia, atherosclerosis and a procoagulant phenotype. Prior prolonged exposure to glucocorticoids also may have irreversible effects on the central nervous system, leading to persistent cognitive and mood alterations. Osteoporosis and fractures, especially vertebral fractures, can further add to morbidity and a poor quality of life. Normalization of cortisol levels leads to significant improvement in comorbidities but long-term data regarding complete resolution are lacking and need further study. CONCLUSION: Early diagnosis and treatment of hypercortisolemia, aggressive management of comorbidities along with long-term follow-up is crucial for the optimal recovery of these patients.